A novel cathode material based on polystyrene with pendant TEMPO moieties obtained via click reaction and its use in rechargeable batteries - Sertkol, Sumeyye Bahceci; Sinirlioglu, Deniz; Esat, Burak; Muftuoglu, Ali Ekrem (SPRINGER, 2015)
In the present study, a new type of cathode-active polymeric material was synthesized via a synthetic strategy which involves a series of high-yield and simple chemical reactions performed on a commercially available and relatively cheap polymer, poly(p-chloromethylstyrene). Polymeric support for the electro-active TEMPO was obtained by nitroxide-mediated polymerization (NMP) of p-chloromethyl styrene. This polystyrene derivative was converted to a polymer with pendant electro-active TEMPO radical groups via an azidation reaction which was followed by a click reaction with an alkyne functionalized TEMPO derivative. The obtained polystyrene bearing TEMPO radical polymer possessed a high spin density of 1.4x10(21) spin/g indicating that electro-active TEMPO groups were successfully attached to the polymer with high yield. The composite cathode material obtained by mixing this TEMPO functionalized polymer with graphite showed a reversible electrochemical redox behavior in a cyclic voltammetry (CV) study vs. Li metal anode. The Li-battery constructed using this cathode maintained 83 % of the its initial capacity (35 mAh/g) over 80 cycles with a cell potential of 3.8 V.
Keywords: Rechargeable; Organic; Polymer; Battery; Click reaction; Cathode; LITHIUM BATTERIES; Polymer Science